Psychometric property evaluation of a midlife women quality of life questionnaire - Putnam, Kathleen (International Journal of Advanced Nursing Studies, 2014)
Background: Quality of life in midlife women may be negatively impacted by biopsychosocial factors including midlife developmental tasks and hormonal changes. Many instruments measure physical aspects of menopause, but few specifically measure global quality of life in midlife women within a biopsychosocial perspective. Objectives: The purpose of this study was to assess the reliability and validity of the Midlife Women Quality of Life Questionnaire (MWQOL). Methods: The original 30-item MWQOL was piloted with a sample of 166 midlife women. Items were derived from the literature and the investigator’s practice experience with this population, which supports the content validity of the instrument. After psychometric evaluation of the first version, 201 midlife women aged 45-64 completed the revised 17-item instrument. Principal component analysis with varimax rotation was used in the factor analysis to determine the construct validity of the MWQOL. Concurrent administration of the Utian Quality of Life (UQOL) instrument was used to determine convergent validity. Results: Three factors emerged from the MWQOL: physical (Cronbach’s alpha 0.82), generativity (Cronbach’s alpha 0.82), and resolution (Cronbach’s alpha 0.78). Two identical items on the MWQOL and the UQOL (“I feel physically fit”) correlated at 0.863. Additionally, 56.5% of the variance in the 17 items of the MWQOL was accounted for by these three factors. Pearson’s correlation between the MWQOL and the UQOL instrument was significant at .768. Conclusions: Findings suggest that the MWQOL is a valid and reliable measure of quality of life for a sample of midlife women. Measures that will improve understanding of the psychological, social, and physical health of midlife women could help providers better evaluate midlife women’s quality of life and assess the effectiveness of specific interventions aimed at improving it. Keywords: Middle Aged, Quality Of Life, Reliability, Validity, Women’s Health.